HUBUNGAN GAMBARAN FOTO WATERS DAN GEJALA KLINIK PADA PENDERITA DENGAN DUGAAN SINUSITIS MAKSILARIS DI RSUP PROF DR. R. D. KANDOU MANADO PERIODE 1 OKTOBER 2012–30 SEPTEMBER 2013 - Wardani, Ni Kadek Ayu Isyana (Universitas Sam Ratulangi, 2014)
Abstract: Sinusitis is an inflamation of Mukosa Paranasal Sinuses in which is determined as the cause for the distraction of human's health that often be suffered by human being in the entire of the world. The well-known sinusitis found is maxillary sinusitis and etmoidalis sinusitis . There are some clinic examination can be done to suspect the existence of maxillary sinus such as anamnesis, physical inspection and radiologi inspection. An inspection through Photo Waters is usually being done to evaluate the infection of paranasal sinus, giving an appropriate evaluation moreover to the minor disease on kovum sinus. The main purpose of this research is to find out the relationship between the description of photo waters and the clinic symptom on the patients with the suspicious of maxillary sinusitis in RSUP prof. Dr.R.D. Kandou manado period of time 1 october 2013-30 september 2013. This research concerns to the analytic correlatic retrospective. The data is collected from sheet of paper in which shows the symptom clinic of maxillary sinusitis and the result of the description of the Photo Waters. Based on the test of correlation Kendal'tau_b the significant value of (p) = 0,272 > 0,05 and the correlation coefficient (r) = 0,150 in which shows that there is a weak positive relationship with the low test value between the description of Photo Waters and clinic symptom on the patients suspicious for maxillary sinusitis. Keywords: Maxillary sinusitis, Clinical symptoms, Photo Waters Abstrak: Sinusitis adalah inflamasi mukosa sinus paranasal yang dianggap sebagai salah satu penyebab gangguan kesehatan tersering diseluruh dunia. Sinusitis yang paling sering di temukan ialah sinusitis maksilaris dan sinusitis etmoidalis. Ada berbagai pemeriksaan klinik yang dapat dilakukan untuk mencurigai adanya sinusitis maksilaris seperti anamnesis, pemeriksaan fisik dan pemeriksaan radiologi. Pemeriksaan Foto Waters adalah pemeriksaan yang paling sering digunakan untuk mengevaluasi infeksi sinus paranasal, memberikan evaluasi yang tepat meskipun pada kelainan ringan pada kavum sinus. Tujuan penelitian ini adalah mengetahui hubungan gambaran Foto Waters dan gejala klinik pada penderita dengan dugaan sinusitis maksilaris di RSUP Prof DR. R. D. Kandou Manado Periode 1 Oktober 2012–30 September 2013. Penelitian ini adalah penelitian analitik korelatik retrospektif. Data berupa lembaran gejala klinik sinusitis maksilaris dan hasil gambaran Foto Waters. Berdasarkan uji korelasi Kendall'tau_b nilai signifikan (p) = 0,272 > 0,05 dan koefisien korelasi (r) = 0,150 yang berarti bahwa ada hubungan positif lemah dengan nilai kemaknaan yang rendah antara gambaran Foto Waters dan gejala klinik pada penderita dengan dugaan sinusitis maksilaris. Kata kunci: Sinusitis maksilaris, Gejala klinik, Foto Waters.